High-strength oxide dispersion strengthened austenitic stainless steel and preparation method thereof

During the preparation of austenitic stainless steel, the oxide powder and process control agent are uniformly mixed with atomization powder and ball milling processes, and cured through thermal isostatic pressing process, the problem of uneven distribution of nano oxides is solved, and the preparation of high-strength oxide diffusion strengthened austenitic stainless steel is achieved, which improves its high-temperature mechanical properties and irradiation swelling properties.

CN119843173APending Publication Date: 2025-04-18INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411903441.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing Fe-Cr-Ni-based austenitic stainless steel has poor irradiation swelling resistance in high-temperature irradiation environments, and the nano-oxides are unevenly distributed in the ball milling process, which affects the microstructure and performance of the alloy.

Method used

By preparing prealloy powder in atomizing powder making device, mixing it uniformly with oxide powder and solid process control agent (such as stearic acid), ball milling under gas protection, and finally curing from powder to alloy through thermal isostatic pressing process to ensure uniform distribution of Y-Ti-O nanooxides in stainless steel.

Benefits of technology

The uniform distribution of Y-Ti-O nanooxides in austenitic stainless steel is achieved, which improves the room temperature and high temperature mechanical properties of the alloy, improves the irradiation swelling performance, and improves the processability of the stainless steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843173A_ABST
    Figure CN119843173A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of powder metallurgy, in particular to high-strength oxide dispersion strengthened austenitic stainless steel and a preparation method thereof. The stainless steel comprises the following components in percentage by mass: 0.1 to 1.5 percent of Y, 0.2 to 2.0 percent of Ti, 0.2 to 5.0 percent of Mn, 0.0 to 4.0 percent of W, 0.0 to 1.0 percent of V, 9.0 to 25.0 percent of Cr, 8.0 to 40.0 percent of Ni and the balance of Fe. The preparation method comprises the following steps: (1) preparing pre-alloyed powder containing the components in an atomizing manner by using an atomizing powder preparation device according to the components; (2) uniformly mixing the pre-alloyed powder with a proper amount of oxide powder and a proper amount of solid process control agent, and carrying out ball milling under the protection of gas to obtain mechanical alloyed powder; and (3) the ball-milled alloy powder is subjected to vacuum packaging, and solidification from the powder to the alloy is achieved through hot isostatic pressing. By using the method, the dispersed and precipitated Y-Ti-O phase nano oxide with small particle size can be obtained, so that the ODS stainless steel has excellent high-temperature mechanical property and strong plasticity matching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy, in particular to a high-strength oxide dispersion-strengthened austenitic stainless steel and a preparation method thereof. Background Art

[0002] Fe-Cr-Ni austenitic stainless steels represented by 316 and 1515Ti have become candidate materials for new nuclear energy system structural materials due to their excellent high-temperature creep resistance, outstanding oxidation / corrosion resistance and mature processability. However, the main problem of Fe-Cr-Ni stainless steels at this stage is the poor resistance to radiation swelling caused by their FCC structure, which cannot be used in nuclear power environments above 550°C for a long time. Therefore, scientists try to use chemically inert, nano-scale, high-density precipitated oxide particles to replace carbon, nitrides and large-sized γ' phases precipitated at grain boundaries, and use the high-energy interface between nano-oxides and the matrix to capture the displaced atoms and helium bubbles generated by radiation, inhibit the aggregation of small helium bubbles at the grain boundaries, and thus make up for the defects of austenitic stainless steel in radiation swelling. At the same time, nanoscale oxide particles are more stable than carbonitrides and γ' phases under high temperature conditions, and can pin matrix dislocations and grain boundary movement, so that oxide dispersion strengthened (ODS) austenitic stainless steel has excellent organizational stability, high temperature mechanical properties and high temperature radiation resistance.

[0003] The main preparation process steps of ODS steel are: pre-alloyed powder and oxide (mainly Y2O3) powder are ball-milled in a high-energy ball mill protected by inert gas (usually high-purity argon), and the uniform diffusion of alloy elements and gas elements between powders is achieved by means of deformation, crushing, cold welding and repeated iterations of the powder, thereby realizing mechanical alloying of the powder. Then, the easy diffusion characteristics of Ti, Y and O elements and the high temperature and high pressure conditions of hot isostatic pressing or hot extrusion processes are used to promote the high-density precipitation of supersaturated Y and O that have been dissolved into the powder lattice in the form of Y-Ti-O or YO, thereby realizing the preparation of high-performance ODS steel. However, the reality is that the Ni element (a must-have element for austenitic stainless steel) makes the alloy powder have strong plasticity and toughness. The Fe-Cr-Ni alloy powder is not easy to break in the ball milling process, and the ball milling powder is mainly deformed. In addition, due to the high temperature environment generated by high-energy ball milling, the ball-milled Fe-Cr-Ni powder is very easy to cold weld between powder and powder, powder and balls, and powder and the wall of the ball mill. While reducing the ball milling powder output rate, it is impossible to achieve effective diffusion of alloy elements, and thus the mechanical alloying of the ball milled powder cannot be achieved. The resulting nano-reinforced phase is unevenly distributed in the ODS steel, the particle size is coarse, and even the machinability of the Fe-Cr-Ni ODS steel is reduced due to the agglomeration of large particles in local areas. In order to avoid cold welding of powder, a process control agent (PCA) can be added in the ball milling process. For example, the preparation patents of ODS nickel-based alloys US 3591362 and US 3809545 mention the use of methanol, liquid hydrocarbons, solutions containing palmitic acid, oleic acid and aluminum nitrate. Patents US 3743548 and US 3865572 use pure benzene and NiCl2. The main problem is that the liquid PCA evaporates in the vacuum process before the inert gas is filled, and it is impossible to fully cover the ball milled powder. At the same time, the introduction of halides pollutes the alloy system, seriously affecting the formation of nano-reinforced phases. Summary of the invention

[0004] Aiming at the problem that the mechanical alloying effect of existing Fe-Cr-Ni series powders is not ideal, which leads to poor microstructure, organizational properties and processability of oxide dispersion strengthened austenitic stainless steel, the purpose of the present invention is to provide a high-strength oxide dispersion strengthened austenitic stainless steel and a preparation method thereof. By using this method, Y-Ti-O nano-oxide with fine particle size and dispersed precipitation can be obtained. The nano-oxide is dispersed in the stainless steel, so that the alloy has excellent room temperature and high temperature mechanical properties.

[0005] The technical solution involved in the present invention is as follows:

[0006] A high-strength oxide dispersion strengthened austenitic stainless steel is composed of the following mass percentages: Y0.1-1.5%, Ti 0.2-2.0%, Mn 0.2-5.0%, W 0.0-4.0%, V 0.0-1.0%, Cr 9.0-25.0%, Ni 8.0-40.0%, and the rest is Fe.

[0007] The high-strength oxide dispersion strengthened austenitic stainless steel is composed of the following mass percentages: Y 0.2-1.0%, Ti 0.2-1.0%, Mn 0.6-2.0%, W 0.8-2.0%, V 0.1-0.6%, Cr 9.0-20.0%, Ni 8.0-30.0%, and the rest is Fe.

[0008] The method for preparing high-strength oxide dispersion-strengthened austenitic stainless steel comprises the following steps:

[0009] Step 1: According to the alloy composition of the stainless steel, a pre-alloyed powder is prepared by atomization using an atomization powder making device;

[0010] Step 2, uniformly mixing the pre-alloyed powder, the oxide powder and the solid process control agent, and ball milling under gas protection to obtain mechanical alloying powder;

[0011] Step three, vacuum packaging the ball-milled alloy powder and solidifying the powder into alloy by hot isostatic pressing.

[0012] The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel comprises the following steps: in step 2, during ball milling, the particle diameter of the pre-alloyed powder and the oxide powder is less than 150 μm; the oxide powder used for mixing is one or more of iron oxide, chromium oxide, nickel oxide, titanium oxide and yttrium oxide, and these powders are adjusted by controlling the dosage of a single or combined powder so as to take into account the adjustment of the matrix element content and the oxygen content; and stearic acid is used as a process control agent for the ball milling process.

[0013] In the method for preparing high-strength oxide dispersion strengthened austenitic stainless steel, in step 2, the amount of stearic acid used as a process control agent is 0.2-2.5% of the total mass of the ball-milled powder.

[0014] In the method for preparing high-strength oxide dispersion strengthened austenitic stainless steel, in step 2, the amount of stearic acid used as a process control agent is 0.4-1.5% of the total mass of the ball-milled powder.

[0015] In the method for preparing high-strength oxide dispersion strengthened austenitic stainless steel, in step 2, the ball-to-material mass ratio of ball milling is 8-20:1, the ball milling speed is 200-350 r / min, and the ball milling time is 33-50 hours.

[0016] In the method for preparing high-strength oxide dispersion strengthened austenitic stainless steel, in step 2, the ball-to-material mass ratio of ball milling is 10-15:1, the ball milling speed is 280-350 r / min, and the effective ball milling time is 45-50 hours.

[0017] In the method for preparing high-strength oxide dispersion strengthened austenitic stainless steel, in step three, the temperature used in the hot isostatic pressing process is 1100-1250°C, the applied pressure is 140-180MPa, the heating rate of the hot isostatic pressing process is 5-15°C / min, and the pressing time is 2-5 hours.

[0018] The high-strength oxide dispersion strengthened austenitic stainless steel preparation method, the nano-oxidation phase precipitated from the obtained stainless steel is a Y-Ti-O phase, and Y-Ti-O phase nanoparticles are dispersed in the stainless steel, which greatly improves the strength of the stainless steel.

[0019] The design concept of the present invention is:

[0020] The present invention controls the amount of process agent added, the ball milling speed and the ball milling time, thereby ensuring that the ball milled powder is fully crushed and then agglomerated, promoting uniform diffusion of elements, and avoiding cold welding of the powder in the early stage of ball milling. The precipitation phase of the high-strength oxide dispersion-strengthened austenitic stainless steel is mainly Y-Ti-O phase nanoparticles, and the Y-Ti-O phase composite nanoparticles play a strengthening role in the alloy.

[0021] In terms of composition design, the Fe-Cr-Ni multi-element alloy with good toughness is used as the matrix, and appropriate amounts of Y and Ti component elements are introduced to achieve the dispersion and precipitation of the reinforcing phase of high-hardness Y-Ti-O phase nanoparticles in the alloy matrix. While ensuring the matching of strength and toughness and strength and plasticity of austenitic stainless steel, the room temperature and high temperature strength of stainless steel is further improved.

[0022] In terms of preparation methods, taking powder metallurgy as the starting point, the benefits of solid process control agents on the ball milling effect of tough Fe-Cr-Ni multi-element alloy powders are clarified, which promotes the uniform diffusion and distribution of alloy elements and gas elements among powders, and then promotes the dispersion and precipitation of Y-Ti-O phase nano-reinforcement phase in the subsequent thermal curing process.

[0023] The advantages and beneficial effects of the present invention are:

[0024] 1) The present invention provides an oxide dispersion strengthened austenitic stainless steel mainly composed of Y-Ti-O phase nanoparticles, which can meet the requirements of Fe-Cr-Ni stainless steel in terms of high-temperature structural stability, high-temperature mechanical properties and high-temperature radiation swelling resistance through the precipitation of nano-scale oxide particles.

[0025] 2) The present invention provides a preparation method for achieving the dispersion and precipitation of nano-oxide particles in an alloy matrix. At the same time, by adjusting the content of mixed oxide powder, the oxygen content in ODS austenitic stainless steel is effectively controlled. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The SEM morphology of the powder surface and cross section of Example 1 without process control agent during ball milling, and with 0.5% toluene and 0.5% stearic acid as process control agents. Among them, (a) SEM morphology of the powder surface without PCA, (b) SEM morphology of the powder cross section without PCA, (c) SEM morphology of the powder surface with 0.5% toluene added, (d) SEM morphology of the powder cross section with 0.5% toluene added, (e) SEM morphology of the powder surface with 0.5% stearic acid added, (f) SEM morphology of the powder cross section with 0.5% stearic acid added.

[0027] Figure 2 This is the electron backscatter diffraction (EBSD) grain structure of the hot isostatically pressed ODS Fe-Cr-Ni austenitic stainless steel in Example 2.

[0028] Figure 3 This is a transmission electron microscope (TEM) image of the nano-strengthening phase distribution in the hot isostatically pressed ODS austenitic stainless steel of Example 3.

[0029] Figure 4 This is a high-resolution TEM (HRTEM) image of the nano-reinforced phase distribution in the hot isostatically pressed ODS austenitic stainless steel of Example 3.

[0030] Figure 5 This is the Fourier transform diffraction pattern of the nano-strengthening phase distribution in the hot isostatically pressed ODS austenitic stainless steel of Example 3.

[0031] Figure 6 It is the tensile curve of the ODS austenitic stainless steel at 650°C in Example 1, and the conventional 316 stainless steel is used for comparison. DETAILED DESCRIPTION

[0032] In the specific implementation process, the present invention proposes a high-strength oxide dispersion strengthened austenitic stainless steel and a preparation method thereof. The stainless steel is composed of Y 0.1-1.5%, Ti 0.2-2.0%, Mn 0.2-5.0%, W 0.0-4.0%, V 0.0-1.0%, Cr 9.0-25.0%, Ni 8.0-40.0%, and the rest is Fe. The preparation steps include: (1) using an atomizing powder making device to atomize and prepare a pre-alloyed powder containing the above components according to the above components; (2) uniformly mixing the pre-alloyed powder with an appropriate amount of oxide powder and an appropriate amount of solid process control agent, and ball milling under gas protection to obtain mechanical alloying powder; (3) vacuum packaging the ball-milled alloy powder, and realizing the solidification of the powder into alloy by hot isostatic pressing.

[0033] The present invention is further described in detail below through examples and drawings.

[0034] Example 1 Comparative Experiment

[0035] The powder with the composition (mass percentage, the same below) of Fe-16.0Cr-14.0Ni-2.0W-1.5Mn-0.4V-0.4Ti was prepared by atomization using the Hunan Jiutai JT-CSBWHI ultrasonic gas atomization powder making device. After the powder was screened, 1kg of powder with a size less than 150μm was mixed with 5.0 grams of Y2O3 powder with a size of 30-50nm, and the powder was milled for 48 hours using a high-energy ball mill under the conditions of high-purity Ar gas (purity 99.999%) protection, ball-to-material mass ratio of 10:1 (grinding ball material is stainless steel, grinding ball diameter is 10mm), and rotation speed of 300r / min. Then, the mechanical alloying powder was vacuum packaged, heated to 1150℃ at a rate of 10℃ / min, and hot isostatically pressed for 3 hours under a pressure of 160MPa to obtain ODS austenitic stainless steel. Calculated by mass percentage, the composition of ODS austenitic stainless steel is Fe-16.0Cr-14.0Ni-2.0W-1.5Mn-0.4V-0.4Ti-0.5Y2O3.

[0036] For comparison, the powder ball milling process was carried out in three groups: (1) without adding process control agent; (2) adding 5 g toluene (~0.5 wt%) as process control agent; (3) adding 5 g stearic acid (~0.5 wt%) as process control agent. After ball milling, the powder was taken for SEM observation ( Figure 1 ).from Figure 1The results show that the ball-milled powder without process control agent was not broken, but deformed, and element diffusion had not yet begun; the ball-milled powder with 0.5wt% toluene as process control agent was only broken and cold-welded on the outer surface, and the powder interior was still a powder cell structure, and the elements inside the powder had not yet begun to diffuse, and the mechanical alloying effect was not good. The Fe-Cr-Ni powder with 0.5wt% stearic acid added was completely broken, and clusters occurred after ball milling, which was conducive to the diffusion of elements between powders and the realization of mechanical alloying.

[0037] Example 2

[0038] In this embodiment, the composition of the high-strength ODS austenitic stainless steel is: Fe-10.0Cr-30.0Ni-0.6Mn-0.1V-0.3Ti-0.25Y2O3, calculated by mass percentage.

[0039] The powder with the composition of Fe-10.0Cr-30.0Ni-0.6Mn-0.1V-0.2Ti-0.2Y was prepared by atomization using a JT-CSBWHI ultrasonic gas atomization powder making device according to the mass percentage. After the powder was screened, 3kg of powder with a size less than 100μm was mixed with 5.0g of TiO2 powder with a size less than 80μm and 45g of stearic acid, and ball milled for 50 hours using a high-energy ball milling device under the conditions of high-purity argon (purity 99.999%), a ball-to-material mass ratio of 12:1 (the ball material is stainless steel, and the ball diameter is 10mm), and a rotation speed of 350r / min. Then, after the ball milled powder was vacuum packaged, the temperature was raised to 1200℃ at a rate of 15℃ / min, and hot isostatic pressing was performed for 4 hours under a pressure of 140MPa to obtain high-strength ODS austenitic stainless steel.

[0040] like Figure 2 As shown in the EBSD microstructure of ODS austenitic stainless steel after hot isostatic pressing, the material pressed at 1200℃ has a very fine grain size, which does not exceed 5μm. Compared with conventional austenitic stainless steel, the grain size is greatly reduced, which is mainly due to the inhibition of grain boundary movement by Y-Ti-O phase nanoparticles generated during the thermal solidification process, indicating that the nano-precipitated phase has a strong pinning effect on dislocations and grain boundaries during plastic deformation, which can play a role in mechanical strengthening.

[0041] Example 3

[0042] In this embodiment, the composition of the high-strength ODS austenitic stainless steel is: Fe-20.0Cr-9.0Ni-1.0W-1.0Mn-0.3V-0.8Ti-1.0Y2O3, calculated by mass percentage.

[0043] The powder with the composition of Fe-20.0Cr-9.0Ni-1.0W-1.0Mn-0.3V-0.8Ti was prepared by atomization using a JT-CSBWHI ultrasonic gas atomization powder making device according to the mass percentage. After the powder was screened, 5kg of powder with a size less than 100μm was mixed with 50g of Y2O3 powder with a size of 3-5μm and 50g of stearic acid, and ball milled for 46 hours using a high-energy ball milling equipment under the conditions of high-purity Ar gas (purity 99.999%) protection, ball-to-material mass ratio of 15:1 (grinding ball material is stainless steel, grinding ball diameter is 12mm), and rotation speed of 290r / min. Then, after the ball milled powder was vacuum packaged, the temperature was raised to 1175℃ at a rate of 10℃ / min, and hot isostatic pressing was performed for 4 hours under a pressure of 160MPa to obtain high-strength ODS austenitic stainless steel.

[0044] like Figure 3 As shown in the TEM characterization results of ODS austenitic stainless steel after hot isostatic pressing, nano-oxides are dispersed and precipitated in the hot isostatically pressed alloy, with small sizes and particle diameters between 2.5 and 10 nm. Figure 4-Figure 5 As shown, HRTEM and Fourier transform diffraction spots prove that the nano-oxide is Y-Ti-O phase nanoparticles.

[0045] Example 4

[0046] In this embodiment, the composition of the high-strength ODS austenitic stainless steel is, by mass percentage, Fe-16.0Cr-14.0Ni-2.0W-1.5Mn-0.2V-0.5Ti-0.5Y2O3.

[0047] The preparation process of high-strength ODS austenitic stainless steel is consistent with the preparation process of Example 1, and stearic acid is used as the process control agent for powder ball milling. The hot isostatic pressed ingot is subsequently machined and tested for mechanical strength at 650°C. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that compared with the mechanical properties of conventional 316 stainless steel at 650°C, the yield strength and tensile strength of ODS austenitic stainless steel have doubled with very small plastic deviation, which is mainly due to the strong pinning of grain boundaries and dislocations by Y-Ti-O phase nanoparticles obtained by this preparation method. At the same time, the stainless steel prepared by this preparation method shows excellent strength-plasticity matching.

[0048] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to allow researchers familiar with this technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength oxide dispersion-strengthened austenitic stainless steel, characterized in that: The stainless steel is composed of the following mass percentages: Y 0.1-1.5%, Ti 0.2-2.0%, Mn 0.2-5.0%, W 0.0-4.0%, V 0.0-1.0%, Cr 9.0-25.0%, Ni 8.0-40.0%, and the rest is Fe.

2. The high-strength oxide dispersion strengthened austenitic stainless steel according to claim 1, characterized in that: The stainless steel is composed of the following mass percentages: Y 0.2-1.0%, Ti 0.2-1.0%, Mn 0.6-2.0%, W 0.8-2.0%, V 0.1-0.6%, Cr 9.0-20.0%, Ni 8.0-30.0%, and the rest is Fe.

3. A method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 1 or 2, characterized in that: The steps include: Step 1: According to the alloy composition of the stainless steel, a pre-alloyed powder is prepared by atomization using an atomization powder making device; Step 2, uniformly mixing the pre-alloyed powder, the oxide powder and the solid process control agent, and ball milling under gas protection to obtain mechanical alloying powder; Step three, vacuum packaging the ball-milled alloy powder and solidifying the powder into alloy by hot isostatic pressing.

4. The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 3, characterized in that: In step 2, during ball milling, the particle diameter of the pre-alloyed powder and the oxide powder is less than 150 μm; the oxide powder used for mixing is one or more of iron oxide, chromium oxide, nickel oxide, titanium oxide and yttrium oxide, and these powders are adjusted by controlling the amount of single or combined powders to take into account the adjustment of matrix element content and oxygen content; stearic acid is used as a process control agent for the ball milling process.

5. The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 4, characterized in that: In step 2, the amount of stearic acid used as a process control agent is 0.2-2.5% of the total mass of the ball-milled powder.

6. The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 4, characterized in that: In step 2, the amount of stearic acid used as a process control agent is 0.4-1.5% of the total mass of the ball-milled powder.

7. The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 3, characterized in that: In step 2, the ball-to-material mass ratio of the ball mill is 8-20:1, the ball mill speed is 200-350 r / min, and the ball mill time is 33-50 hours.

8. The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 3, characterized in that: In step 2, the ball-to-material mass ratio of the ball mill is 10-15:1, the ball mill speed is 280-350 r / min, and the effective ball milling time is 45-50 hours.

9. The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 3, characterized in that: In step three, the temperature used in the hot isostatic pressing process is 1100-1250° C., the applied pressure is 140-180 MPa, the heating rate of the hot isostatic pressing process is 5-15° C. / min, and the pressing time is 2-5 hours.

10. The method for preparing high-strength oxide dispersion strengthened austenitic stainless steel according to claim 3, characterized in that: The nano-oxidation phase precipitated in the obtained stainless steel is a Y-Ti-O phase, and Y-Ti-O phase nanoparticles are dispersed in the stainless steel, which greatly improves the strength of the stainless steel.

Citation Information

Patent Citations

  • Composite metal powder

    US3591362A

  • Dispersion hardened metals having improved oxidation characteristics at elevated temperature

    US3743548A

  • Superalloys by powder metallurgy

    US3809545A

  • Mechanical alloying and interdispersion cold bonding agents therefor

    US3865572A

Cited By

  • Oxide dispersion strengthened fcc metallic material and method of making

    CN122702999A